Android-Based Augmented Reality in Education Activity for Children - Suci Febrina; Lili Rusdiana; Rosmiati Rosmiati (LPPM Universitas Islam 45 Bekasi, 2020)
Augmented reality technology has been widely developed and implemented in an Android-based smartphone application. This technology can be used for entertainment and education. Unfortunately, the use of education is still rare. This paper proposes an android application to introduce the types of land transportation based on augmented reality technology which is visualized in 3-dimensional (3D) form for education as well as entertainment. There are seven land transportation modes that are presented range from two wheels to four wheels, i.e. cars, ambulances, buses, motorbikes, taxis, trucks, and bicycles. Alpha testing has been carried out and shows the results that the application runs well following the expected function. This application can be delivered to the public, especially for the online learning of children in a pandemic situation. In addition, it helps parents to introduce several land transportation modes. With a 3D view, the introduction of types of land transportation is more interactive and realistic. Keywords: android, application, augmented reality, transportation